Influence of Competence and Workload on Employee Performance Mediated by Work Culture in Tanah Bumbu - Marta Tri Susanti; Misransyah Akos; Septeria Noor Yuliannisa; Ali Khamdan (Universitas Muhammadiyah Makassar, 2026)
Employee performance in public sector organisations is influenced by several human resource factors, particularly competence, workload, and work culture. This study aims to examine the direct and indirect effects of competence and workload on employee performance, with work culture acting as a mediating variable, at the Environmental Service Office of Tanah Bumbu Regency. A quantitative approach with a correlational research design was employed. The population consisted of 102 employees, and 50 respondents were selected through random sampling. Data were collected using structured questionnaires and analysed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that competence has a significant positive effect on employee performance (β = 0.390, t = 4.776, p < 0.05). Workload also significantly influences employee performance (β = 0.373, t = 3.680, p < 0.05), while work culture has a significant positive effect on performance (β = 0.386, t = 5.270, p < 0.05). Furthermore, competence does not significantly affect work culture (β = 0.187, t = 1.386, p > 0.05), whereas workload significantly affects work culture (β = 0.623, t = 5.555, p < 0.05). The mediation analysis reveals that work culture does not mediate the relationship between competence and employee performance. However, work culture significantly mediates the relationship between workload and employee performance. The model explains 93.5% of the variance in employee performance and 53.7% of the variance in work culture